Mental Health, Wellness, and Childhood Overweight/Obesity - Shelly Russell-Mayhew; Gail McVey; Angela Bardick; Alana Ireland (Hindawi Limited, 2012)
Childhood obesity is a growing concern, and while progress has been made to understand the association between multiple biological factors (i.e., genetics, nutrition, exercise etc.), little is known about the relationship between mental health and childhood obesity. In this paper, we offer a review of current evidence about the association between mental health and childhood obesity. A systematic literature search of peer-reviewed, English-language studies published between January 2000 and January 2011 was undertaken and resulted in 759 unique records, of which 345 full-text articles were retrieved and 131 articles were included. A theoretical model is proposed to organize the paper and reflect the current state of the literature and includes psychological factors (i.e., depression and anxiety, self-esteem, body dissatisfaction, eating disordered symptoms, and emotional problems); psychosocial mediating variables (i.e., weight-based teasing and concern about weight and shape), and wellness factors (i.e., quality of life and resiliency/protective factors). We conclude with a number of recommendations to support the creation of solutions to the rise in childhood obesity rates that do not further marginalize overweight and obese children and youth and that can potentially improve the well-being of all children and youth regardless of their weight status.